Politeness, impoliteness and ritual maintaining the moral order in interpersonal interaction - Kádár, Dániel Z. 1979-
This book introduces the reader to how people use ritual practices in interpersonal interaction, and politeness and impoliteness situated in/triggered by such practices. It fills an important knowledge gap by offering a framework of politeness that can be used across languages and cultures in the context of ri